Perfect quintuple layer Bi₂Te₃ nanowires: Growth and thermoelectric properties - Schoenherr, P; Kojda, D; Srot, V; Fischer, S; van Aken, P; Hesjedal, T (American Institute of Physics, 2017)
Bi2Te3 nanowires are promising candidates for thermoelectric applications. Vapor-liquid-solid growth of these nanowires is straightforward, but the traditional Au-catalyzed method is expected to lead to Au contamination and subsequently crystal defects. Here, we present a comparison of the Au-catalyzed growth method with an alternative method using TiO2. We observe that the latter approach results in perfect quintuple layer nanowires, whilst using Au leads to mixed quintuple and septuple layer structures. Despite these differences, we surprisingly find only a negligible effect on their thermoelectric properties, namely conductivity and Seebeck coefficient. This result is relevant for the further optimization and engineering of thermoelectric nanomaterials for device applications.